Risk Factors For Anemia In Pregnant Women - Selfy Eltry Elvira; Anna Sari Dewi; Wildana Azikin (Jurnal EduHealth, 2023)
Anemia is a condition of decreased hemoglobin, hematocrit and erythrocyte count below normal values. Anemia in pregnancy is called "Potential Danger to Mother and Child" which plays a role in increasing the prevalence of maternal mortality and morbidity. In pregnancy, pregnant women are said to be anemic if the hemoglobin concentration is less than 11.0 g/dL in the first trimester and less than 10.5 or 11.0 g/dL in the second or third trimester (depending on the guidelines used). Risk factors for anemia in pregnant women are divided into 3 basic factors, namely socioeconomic conditions, education and knowledge, indirect factors, namely ANC visits, parity, nutritional status, age and pregnancy distance, and direct factors of iron (Fe) tablet consumption patterns, infectious diseases and bleeding.